Development of novel dabai pulp-based marker ink: optimization of process configurations, physico-chemical properties, and morphological analysis - Hamzah, Muhammad Hazwan; Anak Surik, Sheralyn Rimba; Aili Hamzah, Adila Fazliyana; Mohd Basri, Mohd Salahuddin; Shamsudin, Rosnah; Mohd Nor, Mohd Zuhair; Md Ali, Abd Halim (Springer Science and Business Media Deutschland, 2025)
This work aims to investigate the development and optimization of a novel dabai pulp-based marker ink using response surface methodology (RSM) with a central composite design. The production of dabai pulp-based marker ink was conducted using dabai pulp powder within the range of 50 to 100 g, glycerol from 15 to 62.5 mL, and carboxymethyl cellulose (CMC) between 1 and 12.5 g, aiming to achieve the desired ink properties of viscosity and color lightness. The results from RSM revealed that the optimal conditions for producing dabai pulp-based marker ink were 12.5 g of CMC, 15 mL of glycerol, and 50 g of dabai pulp powder. The viscosity and color lightness of the optimized dabai pulp-based marker ink with glycerol were compared to those of dabai pulp-based ink without glycerol and commercial ink. The results showed that the viscosity and color lightness of the dabai pulp-based marker ink without glycerol and the commercial ink were 542.73 mPa∙s and 33.15 L*, and 784.03 mPa∙s and 23.92 L*, respectively. Thermogravimetric analysis revealed that the commercial marker ink had the fastest drying rate among the three samples. Fourier transform infrared spectroscopy confirmed the presence of functional groups associated with the dabai pulp-based marker ink. Morphological analysis indicated that dabai pulp powder with glycerol exhibited aggregation, resulting in a much smoother and flatter surface. Overall, dabai pulp-based marker ink shows promise as a viable and innovative material for non-food applications.